2014
DOI: 10.1111/jgs.12760
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Palliative Care into Geriatrics in a Chinese Culture Society—Results of a Collaborative Model between Palliative Medicine and Geriatrics Unit in Hong Kong

Abstract: model reduces the prevalence of falls and injuries and improves secondary outcome measurements.The number of reported fractures decreased from before to after the intervention. This could be a result of numerous contributing factors, including medication, environmental awareness, and improvement in physical fitness. Examining adherence to medication recommendations in particular, showed that 15 individuals were identified for prescription of medication to treat osteoporosis. Sixty-seven percent fully complied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 7 publications
1
21
0
Order By: Relevance
“…Cultural influences were also identified in a study of dying patients in Hong Kong, many of whom desire to die at home [ 58 ]. Only 2.7 % of patients died at home, however, largely due to the influence of social and culture barriers including limited housing, crowded living environments, and perceived threat of devaluing real estate property should a death occur at home [ 58 ]. The same study identified social and cultural taboos (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultural influences were also identified in a study of dying patients in Hong Kong, many of whom desire to die at home [ 58 ]. Only 2.7 % of patients died at home, however, largely due to the influence of social and culture barriers including limited housing, crowded living environments, and perceived threat of devaluing real estate property should a death occur at home [ 58 ]. The same study identified social and cultural taboos (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The same study identified social and cultural taboos (e.g. idea that speaking about death may bring upon death) has significant influencers on perceptions of ‘a good death’ [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite increases in the use of palliative and hospice care in elderly patients with terminal illness, ethnic disparities persist [ 33 ]. Therefore, hospice care teams who understand cultural differences between Chinese and Western societies might improve EOL quality care.…”
Section: Discussionmentioning
confidence: 99%
“…In Hong Kong, given the crowded living arrangements, and the perception that deaths in the home will lower the value of the real estate in a country where housing is extremely expensive (H. W. Cheng, Li, Chan, Ho, & Sham, 2014), only 31% of the surveyed Hong Kong public opted to die at home (R. Y. Chung et al, 2017).…”
Section: Preferences In Asian Countriesmentioning
confidence: 99%
“…W. Cheng et al, 2014), Shifting care from the hospital to the home requires the home space to be large enough to accommodate medical technologies and services to support home-based care. In certain urban environments such as Hong Kong (Tse, Chan, Lam, Leu, & Lam, 2007),, home deaths may not be practical due to space limitations.…”
Section: The Hong Kong Experiencementioning
confidence: 99%